Determination of the Interest of University Students Studying Sports towards Sports Startups Initiatives - Şimşek, Abdullah; Devecioğlu, Sebahattin (Uluslararası Bilim Kültür ve Spor Derneği (UBİKS), 2025)
The aim of the research is to determine the interest of university students studying sports at undergraduate level towards sports startups. The data collection tool in the research consists of two parts; the first part includes the Personal Information Form consisting of 7 questions, while the second part uses the Sports Startups Interest Scale developed by the researcher, consisting of 21 questions and 6 sub-dimensions. While the population of the research consists of students receiving sports education in Turkey, the sample consists of 1409 students. The data obtained in the research were transferred to the licensed SPSS 21.0 programme. Before the analyses were performed, normality analysis was performed and it was determined that the data obtained showed normal distribution. Then, percentage, frequency and standard deviation values were determined in terms of the variables determined in the research. Due to the normal distribution of the data obtained, independent simple t-test and one-way variance (ANOVA) tests were preferred in the research. Pearson correlation test was applied to determine the relationships between the sub-dimensions of the sports startups interest scale and the total average of the scale. As a result of the answers given by university students studying sports to the sports startups interest scale, it is concluded that there is no significant difference between the variables of gender, age, department, monthly household income, while it is concluded that there is a significant difference in the variables of university, class and startup usage.

Araştırmanın amacı, lisans düzeyinde spor eğitimi alan üniversite öğrencilerinin spor girişimlerine yönelik ilgilerini belirlemektir. Araştırmada veri toplama aracı iki bölümden oluşmaktadır; birinci bölümde 7 sorudan oluşan Kişisel Bilgi Formu, ikinci bölümde ise araştırmacı tarafından geliştirilen 21 soru ve 6 alt boyuttan oluşan Spor Girişimlerine Yönelik İlgi Ölçeği kullanılmıştır. Araştırmanın evrenini Türkiye'de spor eğitimi alan öğrenciler oluştururken, örneklem 1409 öğrenciden oluşmaktadır. Araştırmada elde edilen veriler lisanslı SPSS 21.0 programına aktarılmıştır. Analizler yapılmadan önce normallik analizi yapılmış ve elde edilen verilerin normal dağılım gösterdiği tespit edilmiştir. Daha sonra araştırmada belirlenen değişkenler açısından yüzde, frekans ve standart sapma değerleri belirlenmiştir. Elde edilen verilerin normal dağılım göstermesi nedeniyle araştırmada bağımsız basit t-testi ve tek yönlü varyans (ANOVA) testleri tercih edilmiştir. Spora başlama ilgisi ölçeğinin alt boyutları ile ölçeğin toplam ortalaması arasındaki ilişkileri belirlemek için Pearson korelasyon testi uygulanmıştır. Spor eğitimi alan üniversite öğrencilerinin spor girişimleri ilgi ölçeğine verdikleri cevaplar sonucunda cinsiyet, yaş, bölüm, aylık hane geliri değişkenleri arasında anlamlı bir farklılık olmadığı sonucuna ulaşılırken, üniversite, sınıf ve startup kullanımı değişkenlerinde anlamlı bir farklılık olduğu sonucuna ulaşılmıştır.
Spor Eğitimi Alan Üniversite Öğrencilerinin Spor Startupları Girişimlerine Yönelik İlgilerinin Belirlenmesi
Keywords: Sports Science and Exercise (Other); Egzersiz ve Spor Bilimleri (Diğer)